Financial Inclusion and the Linkages to Stability, Integrity and Protection : Insights from the South African Experience - CGAP (World Bank, Washington, DC, 2013)
International Standard-Setting Bodies (SSBs) and national policy makers-including financial regulators-pursue the core objectives of financial stability, financial integrity and financial consumer protection. These advances challenge financial regulators to consider how to optimize the linkages among the four distinct policy objectives financial inclusion, financial stability, financial integrity, and financial consumer protection. There is good reason to believe that, at the level of outcomes, ISIP objectives may be mutually reinforcing and interdependent: no long term stability without inclusion, for example, and vice versa. In practice, at the policy level, the linkages are less well known and policy makers face choices that are unnecessarily framed as tradeoffs. This report introduces and develops the concept that a proportionate approach to any financial inclusion measure (and specifically to its regulatory and supervisory design and implementation) should seek to optimize the ISIP linkages: maximizing synergies and minimizing tradeoffs and other negative outcomes. In South Africa, the four ISIP objectives are also the four pillars of national financial sector policy; and financial inclusion in various forms has been a key objective for the postapartheid period. The study sought to understand in each case: 1) whether the ISIP linkages were considered at the time of the intervention; 2) what was done to mitigate potential ISIP risks; and 3) as far as the available data allowed, what linkages have been manifest to-date.